Sistem Informasi Keuangan Dan Kegiatan Pada Masjid Berbasis Web (Studi Kasus: Masjid Nurul Iman Valencia) - Muhammad Ashgar Mulia; Wasis Haryono (CV. Multi Kreasi Media, 2022)
Nurul Iman Mosque is one of the mosques located in Graha Raya, Valencia Cluster, North Serpong District, South Tangerang City, Banten. Many activities are carried out by the Nurul Iman Mosque, such as religious activities, Islamic holidays, TPA, and other activities. Some of the problems that occur at the Nurul Faith Mosque are that the recording of financial activity in and out is still done manually using a cash book, which has a very large chance of error and is less efficient. Meanwhile, the media for delivering financial transparency, and the schedule of activities that will be carried out by the congregation is only through bulletin boards, where the media is not optimal, so that the information conveyed is not evenly distributed to the public. Therefore, in order to make it easier for mosque administrators to process finances and facilitate the delivery of any activity information to the public, a web-based information system is needed. The Financial and Activity Information System at the mosque that was built can provide input data for input data, donations and expenditures on finance, post articles, and activities carried out by the congregation at the Nurul Iman Mosque. This system is built using the PHP programming language, the database uses MYSQL, and the CodeIgniter Framework. And for the system development method using the Waterfall method as system analysis and design. The Financial and Activity Information System at this Mosque hopes to facilitate religious activities, Islamic holidays, TPA, and other activities.